UNDERSTANDING AND OVERCOMING PARENTAL VACCINE HESITANCY - Alexandru Paul Baciu; Ancuta Lupu; Ginel Baciu; Carmen Baciu; Tatiana Chisnoiu; Lorenza Forna; Vlad Andrei Pitea; Adriana Luminita Balasa; Larisia Mihai; Bianca-Maria Constantin; Ramona Mihaela Stoicescu; Vasile Valeriu Lupu; et al. (Romanian Journal of Oral Rehabilitation)
(1) Background: Vaccination represents one of the most successful interventions worldwide in the field of public health. Immunization is one of the measures with the best results, being extremely efficient compared to all associated costs. Being a preventive measure, immunization relies entirely on the acceptance, understanding, and trust of those who use this service. The purpose of this study is to gather as much data as possible regarding the general opinion parents have regarding vaccines and the vaccination of their children; (2) Methods: For the purpose of this study, a cross-sectional survey was used through the application of a questionnaire employed as a research instrument, consisting of 35 questions. The questionnaires were physically distributed to family medicine cabinets for parents to complete, and the data collection period was throughout the months of May, June, and July of 2022. A total of 200 questionnaires were obtained, and their results were analyzed; (3) Results: The study was conducted on 200 respondents. Approximately two-thirds of the surveyed parents believe that all vaccines are necessary and of great importance. The reasons why parents do not accept certain vaccines were also evaluated within the questionnaire. Many respondents agreed that fear of possible severe adverse effects, as well as lack of correct information about vaccines, are the main issues leading to vaccine refusal. With the data we have gathered, we were able to track the general opinion of parents regarding vaccination, their level of information, the risks they express concern about, the relationship between parents and doctors regarding the vaccination process of their child, as well as their level of confidence in the effectiveness of vaccines; (4) Conclusions: From the general opinion on vaccines, it emerges that they are considered highly important and necessary by the majority of parents. Almost all respondents are interested in accumulating as much information as possible about vaccination. The majority of parents have adhered to vaccination norms, and their children either have received vaccines from the National Immunization Program (NIP) or are scheduled to receive them. The risk of adverse effects remains the primary concern of parents. Parents’ trust in vaccination continues to be a key element in understanding their attitude towards the entire immunization process.